Declining trends in sweetness of the diet in the United Kingdom: 2008/9–2018/19 - Kutepova, Inga; Kamil, Alison; Wilson, Alissa R.; Rehm, Colin D. (Frontiers in Nutrition, 2025)
Sugar reduction is a major public health priority. Due to the assumed correlation between dietary sweetness and sugars intake, some organizations suggest minimizing dietary sweetness regardless of source. Data describing the trends/patterns in the sweetness of the diet may inform dietary recommendations. This cross-sectional study utilized dietary data from 2008/09 to 2018/19, including 15,655 individuals ≥1.5 year from the United Kingdom's National Diet and Nutrition Survey Rolling Program. Products sweetened with low-calorie sweeteners (LCS) were matched to their sugar-sweetened pair (e.g., regular cola vs. diet cola), which was used to estimate the sugar equivalents from LCS-sweetened products and estimate dietary level sweetness, defined as grams of approximate sugar equivalent (ASE) per day. Foods and beverages that underwent reformulation during the study period through the use of LCS were also identified. From 2008/9 through 2018/19, the ASE of the overall UK diet declined by about 10%. LCS products contributed 13% of ASE. There was evidence of a non-linear trend, with ASE levels relatively stable until 2014/15 and then declining. Overall, the decline in ASE was larger for beverages than foods (ASE values declined 20.7% for beverages vs. 4.4% for foods), although both decreased significantly (p-value < 0.01). Dietary sweetness has changed in the UK, due to a combination of consumer behavior, reformulations, policies, public health awareness programs, and media campaigns, emphasizing its multifactorial nature.